A contribution to hazard assessment of combined exposure to mycotoxins using in vitro toxicity testing - Tavares, Ana (2016)
Abstract publicado em: Toxicology Letters. 2015; 238 (2, Suppl.): S352-3. doi:10.1016/j.toxlet.2015.08.1007. Disponível em: http://www.sciencedirect.com/science/article/pii/S037842741502946X